Métiers d’artisan dans les abbayes ardennaises de Saint-Hubert et Stavelot-Malmedy (viie-xiie siècle) - Philippe Mignot (Bulletin du Centre d’Études Médiévales d’Auxerre)
It is interesting to compare Stavelot and Saint-Hubert, the two Benedictine abbeys of Ardennes, distant of about sixty kilometres, in terms of artisanal activities within them. A parallel study of the two abbeys enriches textual and archaeological data relative to one another.If the historical context of their respective foundation is different, the relation with their immediate environment or their more distant domains is almost identical. They were both established away from major thoroughfares, therefore road links were inherently difficult. Yet these roads were essential to their regular food supply.The examination of written and archaeological sources allows us to have some insight of the arts and craft inside the abbeys.